2014
DOI: 10.1039/c4ra00507d
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes of gold nanoparticles due to adsorption onto silicon substrate and oxygen plasma treatment

Abstract: We present comprehensive studies of the morphological evolution that gold nanoparticles undergo during their adsorption on a solid substrate and subsequent oxygen plasma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…In summary, there have been conflicting reports on the impact of oxygen plasma on nanoparticles, but our findings support other observations that oxygen plasma treatments are detrimental to nanoparticles [24,25]. Moreover, we propose the use of UVO to clean heterogeneous Au nanoparticle surfaces with the additional benefit of being a superior technique for preparation of thin film deposition when a hydrophilic surface is required, as in the case of atomic layer deposition of alumina.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In summary, there have been conflicting reports on the impact of oxygen plasma on nanoparticles, but our findings support other observations that oxygen plasma treatments are detrimental to nanoparticles [24,25]. Moreover, we propose the use of UVO to clean heterogeneous Au nanoparticle surfaces with the additional benefit of being a superior technique for preparation of thin film deposition when a hydrophilic surface is required, as in the case of atomic layer deposition of alumina.…”
Section: Discussionsupporting
confidence: 86%
“…However, the comparative impact of these techniques on nanostructured surfaces with different materials exposed (e.g., gold and SiO2) has yet to be examined to the same extent as has been observed for uniform Au films or silicon surfaces. Recently, reports have indicated that oxygen plasma can be destructive to Au nanoparticles (AuNPs) [24,25] but others have argued that the plasma does not alter the AuNP surface or damage only happens under very aggressive conditions [21]. In the case of UVO cleaning of surfaces, early studies were conducted for continuous planar metal films, but the assessment of the impact of UVO cleaning has not been extended to nanostructured surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Note that at nanometer scale the melting point of gold is much lower than the bulk gold (1064 °C). In addition, the plasma treatment itself has been reported to induce morphological changes in gold . In our case, probably the pearling effect already took place during the oxygen plasma cleaning since the chamber temperature increases during the procedure.…”
Section: Resultsmentioning
confidence: 69%
“…We assume the diffusion coefficients to follow the power law: = 1 − , where 1 is the diffusion coefficient of adatoms and is a scaling exponent. Such a law provides a good approximation for several adlayer-substrate systems 31,43,[61][62][65][66][67][68][69] . To calculate the projected radius and the surface area of the clusters, we model them as spherical caps 44 characterized by a contact angle = 2 tan −1 ( / ) , where H/R is the height-to-radius ratio.…”
Section: Thementioning
confidence: 97%